Use of Vandetanib in Metastatic Medullary Carcinoma of Thyroid in a Pediatric Patient With Multiple Endocrine Neoplasia 2B. Issue 2 (March 2016) - Narayanan, Vidya K.; Ronghe, Milind; MacGregor, Fiona B.; Bradshaw, Nicola; Davidson, Rosemarie; Welbury, Richard; Reed, Nicholas; Shaikh, Mohamad G.
Abstract : We describe a child with advanced, metastatic, inoperable medullary carcinoma of thyroid associated with multiple endocrine neoplasia 2B and rearranged during transfection mutation with a positive response to vandetanib treatment. He responded well with a fall in calcitonin levels and a reduction in size of the thyroid malignancy, lymph nodes, and pulmonary metastases. He has been on vandetanib for 4 years with good clinical and biochemical response. Vandetanib has a role in the treatment of patients including children with inoperable locally advanced and metastatic medullary carcinoma of thyroid. More information is needed on its use in children and long-term outcome.